Case Report: Cutaneous metastatic mucin-producing prostate adenocarcinoma - Yildirim, Ahmet M.; Semler, Douglas; Harvell, Jeffrey; Yu, Eun-Mi; Jang, Sekwon; Venna, Suraj (Frontiers in Oncology, 2025)
Cutaneous metastasis of prostate adenocarcinoma is exceedingly rare, accounting for less than 1% of all skin metastases. It typically occurs late in the disease course and often mimics benign or primary skin malignancies. An elderly man with a history of benign prostatic hypertrophy presented for a routine dermatologic examination, during which an ulcerated nodule was identified on his upper back. Histopathology of the lesion revealed a dermal-based malignant glandular tumor. Immunohistochemistry was negative for CK20, CK5/6, PAX-8, TTF-1, PSA, and PIN4, but positive for PSAP and NKX3.1, consistent with mucin-producing prostate adenocarcinoma. Although his recent digital rectal exam was normal and prostate cancer screening had been deferred due to age, further work-up showed elevated serum PSA (30.49 ng/mL) and widespread metastatic disease on PET/CT imaging. He was started on androgen deprivation therapy with relugolix. This case underscores the diagnostic importance of skin biopsies in evaluating atypical lesions and highlights a rare presentation of metastatic prostate adenocarcinoma in an elderly patient with minimal systemic symptoms. It also raises awareness of prostate cancer presenting as solitary cutaneous metastasis and calls attention to the potential value of PSA screening in select elderly patients. Recognizing uncommon cutaneous manifestations may lead to earlier diagnosis and improved management of advanced internal malignancies.